UJI VALIDITAS MEDIA SMARTBOX UNTUK MENINGKATKAN HASIL BELAJAR SISTEM PANCA INDRA MANUSIA - Naela Nabila; Fera Dwidarti; Badri Atul Fikriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to test the validity of the SmartBox interactive learning media developed to improve student learning outcomes in the subject of the human sensory system. SmartBox is an innovative media designed to present information through visual displays, audio, and direct interaction, thereby increasing student engagement and understanding of abstract material. Validation was conducted by three experts: a subject matter expert, a media expert, and a language expert, using a Likert scale-based assessment instrument. This study is a developmental research with a descriptive quantitative approach. Data collection techniques included observation sheets, questionnaires, and validation sheets. The validation results by the language expert showed a score of 100% (very valid category), The validation results by the language expert showed a score of 100% (very valid category), the subject matter expert obtained a score of 72% (valid category), and the media expert obtained a score of 88% (very valid category). The overall average validation score for the SmartBox media was 85%, indicating that this media falls into the ‘valid’ category and is suitable for use in the learning process. Thus, the SmartBox media has been proven to meet the aspects of content, presentation, and technical feasibility, and has great potential to support student learning outcomes in the material on the five senses. These findings are expected to serve as a basis for further development and implementation of interactive media in thematic science learning in primary schools.